Transient lesion in the splenium of the corpus callosum: three further cases in epileptic patients and a pathophysiological hypothesis. Issue 4 (1st April 2001) - Polster, T; Hoppe, M; Ebner, A
Abstract : OBJECTIVE: Focal lesions limited to the splenium of the corpus callosum (SCC) are rare and little is known about their aetiology. Three patients were examined for presurgical evaluation in epilepsy with a transient lesion in the SCC and a pathophysiological hypothesis is presented. METHODS: Three patients were identified with a circumscribed lesion in the centre of the corpus callosum. Follow up MRI was performed, the medical records examined retrospectively, and the literature reviewed. RESULTS: The patients showed identical lesions in the SCC with reduced T1 and increased T2 signal intensity and an unaffected marginal hemline of a few mm. Patients were asymptomatic and control MRIs showed complete normalisation within 2 months. Patients had been treated with antiepileptic drugs (AEDs) without signs of toxicity. In all patients AEDs were rapidly reduced for diagnostic purposes, but only one had psychomotor seizures, 5 days before imaging. CONCLUSIONS: A transient lesion in the SCC has so far only been described in 13 patients with epilepsy and has been interpreted either as reversible demyelination due to AED toxicity or transient oedema after secondary generalised seizures. The data confirm neither of these hypotheses. A transient lesion in the SCC seems to be a non-specific end point of different disease processes leading to a vasogenic oedema. This suggests, in these patients, a multifactorial pathology triggered by transient effects of AEDs on arginine vasopressine and its function in fluid balance systems in a condition of vitamin deficiency. The complete and rapid reversibility in all cases without specific intervention is emphasised and any invasive diagnostic or therapeutic approach is discouraged.